Design for Additive Manufacturing (DFAM) Leveraging 3D Printing to Optimize Machine Components - Amit Shishodia (International Journal of Machine Systems and Manufacturing Technology, 2024)
Design for Additive Manufacturing (DFAM) is a new methodology that focuses on maximizing the special potential of 3D printing technologies to optimize machine components. Contrasting to traditional manufacturing processes, additive manufacturing (AM) makes it feasible to create complicated shapes that would be impossible or difficult to do using standard methods like casting or machining. This study explores the principles of DFAM, including the advantages it offers in terms of design flexibility, material efficiency, and performance optimization. The research highlights how engineers and designers can leverage 3D printing to improve the function, strength, and cost- effectiveness of machine components. Furthermore, it discusses key considerations in DFAM, such as material selection, the impact of part orientation, support structures, and post-processing. To illustrate how DFAM has been utilized efficiently in sectors including aerospace, automotive, and medical devices, instances of use are given. The difficulties and potential paths for DFAM as the technology develops are covered in the conclusion of the study.
Keywords: 3D printing; Additive manufacturing; DFAM; direct metal laser sintering